Ayurvedic management of idiopathic granulomatous mastitis (Sthanavidradhi): A case study (Indian Journal of Case Reports, 2019)
Idiopathic Granulomatous Mastitis (IGM) is described as an uncommon, benign inflammatory breast disease of unknown etiology. Although its exact prevalence is unknown, IGM is considered to be very rare. Here, we report the case of a 36-year-old female who came to our hospital with complaints of pain and lump in the right breast since 2 months. We diagnosed the case as Sthana Vidradhi and vathakaphasamana chikithsa was administered. The wound was managed with vranaropakalepa and kashaya. After treatment, the wound was healed. Pain and tenderness were reduced and the lump was disappeared after two months of medication. The medication continued and complete recovery was noted after 6 months of treatment. The patient was monitored for six months after the complete cure.